Size related processes in phytoplankton - Sandow, Marcel (2004)
Growth, death, respiration, excretion and sedimentation describe the major rate processes of phytoplankton. These rates often scale allometrically (rate=a*mass^b). The allometric coefficient (b) describes the deviation from a linear reltionship. Literature values derived from experiments showed allometric coefficients of -0.48 to -0.1. Experiments with natural phytoplankton communities from the baltic and the subtropical gyre of the North Atlantic ocean showed an allometric coeffcient range of -0.72 to -0.3. The results indicate that size scaling of rate processes in phytoplankton is more pronounced than previously thought.